Effects of aeroelasticity on the performance of hypersonic inlet. (September 2018) - Ye, Kun; Ye, Zhengyin; Zhang, Qing; Qu, Zhan
Effects of the aeroelasticity on the performance of the hypersonic inlet have been investigated numerically in this study. The aeroelasticity has been simulated using the coupled computational fluid dynamics/computational structural dynamics method, which is solved by the in-house code. The unsteady Reynolds-averaged Navier–Stokes equations have been solved in the computational fluid dynamics simulation, and the modal method has been adopted in the computational structural dynamics simulation. Two cases have been utilized to validate the numerical method. Finally, the aeroelasticity has been simulated for inlet plate with different thicknesses. The effects of aeroelasticity on performance parameters and flow structure have been discussed in detail. The results show that the generalized displacements present the "beat" phenomenon in the time domain. The power spectral density of the generalized displacements implies that the aeroelastic instability is mainly caused by the coupling between the fourth- and fifth-order modes. The time-average flow rate coefficient and pressure rise ratio increase relative to the initial value, while the total pressure recovery coefficient decreases. The fluctuation amplitude of the flow rate coefficient is small, while that of the total pressure recovery coefficient and pressure rise ratio are relatively large. Besides, the phases of the three performance parameters are greatly different. Furthermore, the aeroelasticity has significant effect on the shock wave structure especially at the exit of the inlet.